Perancangan Sistem Informasi Manajemen Jam Ganti Guru Menggunakan Round Robin Berbasis Web: Studi Kasus: SMK Parulian 2 Medan - Tri Yulistiani Siregar; Niko Surya Atmaja; Sahyunan Harahap (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
SMK Parulian 2 Medan is a vocational school with 20 teachers managing 6 classes and a total of 180 teaching hours per week. The management of teacher substitution hours is currently still carried out based on direct considerations without using a structured mechanism. This condition gives rise to several problems, namely poorly organized teacher schedule data, the process of determining substitute teachers that takes quite a long time so that it can disrupt teaching and learning activities, and the distribution of substitute hours that is not evenly distributed among teachers. This study aims to design a web-based application for managing teacher substitution hours that is able to organize data in a structured manner, implement fair rotations in the assignment of substitute teachers, and present schedule information that is easily accessible. The proposed method is the Round Robin algorithm, which distributes substitute hour assignments in turns based on a certain order so that each teacher has an equal opportunity to receive additional teaching assignments. The resulting design allows for structured storage of teacher and schedule data in a database, automation of substitute teacher determination using the Round Robin mechanism, and presentation of information through a web-based interface that can be accessed by school administration staff. Compared to the current management method, the design offers more organized data management, faster replacement teacher assignments, and a more balanced distribution of teaching loads. This study concludes that web-based replacement teacher management integrated with the Round Robin algorithm can effectively address scheduling issues at SMK Parulian 2 Medan and improve the continuity of teaching and learning activities